Measles. Characteristics of the Epidemic Process and its Determinant in Real-Time Conditions (on the Example of a Measles outbreak in Yekaterinburg in 2016) - A. A. Golubkova; T. A. Platonova; A. N. Kharitonov; E. A. Rybinskova; E. V. Lelenkova; T. S. Yuzhanina (Эпидемиология и вакцинопрофилактика)
Introduction. Measles still poses a threat to the inhabitants of the planet. In different regions of the world and the Russian Federation are recorded instances of contamination and subsequent infection with formation of foci with a significant number of victims. Measles has a high reproduction rate of the infection. The purpose of this study was to determine the main characteristics of the epidemic process of measles and its determinants in realtime for direct and indirect control of epidemic process. Materials and methods. The authors analyzed the data of official registration of the incidence of measles the population of Ekaterinburg from 1988 to 2016, and medical records of cases of measles in 2016. We used epidemiological, clinical and statistical research methods. Results. The authors found that the epidemic process of measles has undergone significant changes. Measles was not registered in the city from 2001 to 2015, the unit drifts measles-endemic territories didn't leak. However, the situation changed at the end of 2016. It was 72 clinically and laboratory confirmed case of measles in a period of 11 weeks. The largest proportion of cases were in children who are not vaccinated against measles. The average age of infection in children was 3.8 years. 59 measles epidemic foci were formed during the flash. Foci were registered in families, educational institutions and health care organizations. The most active spread of the infection was in medical organizations. The spread was associated with the presence of susceptible children and adults, serious shortcomings in terms of timely diagnostics of measles in the first and subsequent cases, violations in the organization of antiepidemic measures. Conclusion. 1. Despite positive shifts in the direction of measles elimination, it remains an actual infection, reserving opportunities for distribution among unvaccinated adults and children. 2. A special feature of the outbreak of measles in the territory of Yekaterinburg was the spread in medical organizations with the formation of secondary foci along the routes of following sick children and adults. The share of foci in medical organizations was 15.2% of the number of all foci, and the number of cases in any - 70.8% of registered cases.3. The significance of previously vaccinated cases as potential sources of infection in the foci is not high, the incidence rate when in contact with them is 0.53 ± 0.15, whereas in contact with previously not vaccinated - 7.94 ± 0.56.